2011
DOI: 10.1152/ajpheart.01217.2010
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory baroreflex sensitivity in humans is not modulated by chemoreflex activation

Abstract: IL, Ocon AJ, Taneja I, Terilli C, Medow MS. Ventilatory baroreflex sensitivity in humans is not modulated by chemoreflex activation. Am J Physiol Heart Circ Physiol 300: H1492-H1500, 2011. First published February 11, 2011 doi:10.1152/ajpheart.01217.2010.-Increasing arterial blood pressure (AP) decreases ventilation, whereas decreasing AP increases ventilation in experimental animals. To determine whether a "ventilatory baroreflex" exists in humans, we studied 12 healthy subjects aged 18 -26 yr. Subjects under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 58 publications
3
27
0
Order By: Relevance
“…Pharmacologically induced changes in blood pressure not only triggered baroreflex responses in f H but also affected _ V E in R. schneideri, similar to what has been reported for mammals (Brunner et al, 1982;Walker and Jennings, 1998;McMullan and Pilowsky, 2010;Stewart et al, 2011). Increases in blood pressure in the toads were followed by reductions in _ V E , primarily through modification of f R and to a lesser extent V T ; conversely, _ V E was significantly increased during hypotension.…”
Section: Temperature Effects On Cardiorespiratory Reflex Responsessupporting
confidence: 77%
See 1 more Smart Citation
“…Pharmacologically induced changes in blood pressure not only triggered baroreflex responses in f H but also affected _ V E in R. schneideri, similar to what has been reported for mammals (Brunner et al, 1982;Walker and Jennings, 1998;McMullan and Pilowsky, 2010;Stewart et al, 2011). Increases in blood pressure in the toads were followed by reductions in _ V E , primarily through modification of f R and to a lesser extent V T ; conversely, _ V E was significantly increased during hypotension.…”
Section: Temperature Effects On Cardiorespiratory Reflex Responsessupporting
confidence: 77%
“…Generated extravascular fluid in anuran amphibians returns to the cardiovascular system through a combination of changes in pressure and volume of the lymph sacs that is driven by effectors such as lung ventilation (inflation and deflation) and skeletal muscle contraction Hedrick et al, 2007). Therefore, from an evolutionary perspective, ventilatory responses that may be modulated by baroreceptor loading and unloading in R. schneideri can contribute to our understanding of a number of pieces of evidence for the influence of the cardiovascular system on the respiratory system in mammals (Brunner et al, 1982;Walker and Jennings, 1998;Baekey et al, 2010;McMullan and Pilowsky, 2010;Stewart et al, 2011). More interestingly, our findings add further support to a role for lung ventilation in blood pressure/volume homeostasis in anuran amphibians , although the relationship between pulmonary ventilation, baroreflex and lymphatic system in our toads is still correlational rather than mechanistic.…”
Section: Blood Pressure Homeostasis In Anuran Amphibiansmentioning
confidence: 99%
“…Alternatively, β-adrenergic stimulation increases resting ventilation and reflex chemosensitivity [22,23], and baroreflex activity is inversely related to ventilation (i.e. a drop in pressure, as observed in the present study, may elicit an increase in ventilation) [24]. Such an increase in ventilation could reduce arterial PCO 2 and affect global CBF.…”
Section: Discussionsupporting
confidence: 55%
“…Using optogenetics, we have shown that selective C1 neuron stimulation activates breathing in conscious mice (1). Barosensitive C1 neurons presumably contribute to the ventilatory baroreflex; i.e., the breathing stimulation elicited by hypotension, well described in conscious humans (173).…”
Section: C1 Cells Hypotension and Baroreflexesmentioning
confidence: 92%